Hubungan antara Harga Diri dan Body Image dengan Online Self-Presentation pada Pengguna Instagram - Lalu Arman Rozika; Neila Ramdhani (Faculty of Psychology, Universitas Gadjah Mada, 2016)
This research departs from the results of previous studies in the field ofcyberspace, which shows differences in one's behavior when in the world of the internetand in the real world. The Internet has now become the most widely used communicationtool. The purpose of this study is to see what psychological factors that affect a personwhen behaving in the internet world. Subjects in this study were 389 users of Instagramusers who filled out the research questionnaire online. Measuring tool in this research is aself-esteem scale, body image scale, and self-presentation online scale. While the analysismethod used is Multiple Linear Regression Analysis. The results showed that there is apositive relationship between self-esteem and body image with online self-presentation.Self-esteem and body image can predict self-presentation online with a significance levelof p <0.05. Effective contribution of self esteem and body image variable to self-presentation online variable is 3.8%.